PERBANDINGAN DAYA HAMBAT FLUKONAZOL DENGAN MIKONAZOL TERHADAP JAMUR Candida albicans SECARA IN VITRO - Gilang Ramadhan; Praptiwi Hanafi; Ratna Sulistiorini (Universitas Muhammadiyah Semarang, 2017)
Introduction: Candida is a normal microflora in the oral cavity that is reported to be altered from rarely cause infection becomes opportunistic infections. Candidiasis oral prevalence in Indonesia reaches 84% in 2009. Fluconazole is effective for Candida albicans 97, 9%. While topical miconazole therapy results in 92, 8% affectivity with miconazole. Objective: this study intends tocompare the inhibitory power of flukonazole with miconazole to Candida albicans. Method: this research is an experimental research with 32 sampel of Candida albicans divided into 2 groups of treatment i.e with antifungal flukonazol and mikonazol then measured the diameter of inhibition by diffusion methode. The statistical test used the Mann-Whitney. Result: this research showed that fromthe both treatment groups, the fluconazole group showed significant result with the average of mean of inhibition zone 4.33 mm SD 0.218. Whereas miconazole antifungal showed the average of diameter of inhibition zone 1.07 mm and SD 0.112. Conclusion: 100 mg fluconazole antifungal was more effective than 100mg miconazole antifungal against Candida albicans fungi. Keywords: Candida albicans, Fluconazole, Miconazol. Antifungal.